Desperate for digital technology - Yeremina, S.F.; Gordeeva, E.A. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The pandemic has accelerated digital transformation in almost every sector of the economy. Most companies in the European Union and the U.S. expect the COVID-19 outbreak to have a lasting impact on digital use, according to the Digitalization in Europe 2020: Evidence from the EIB Investment Survey. More than a third of companies expect the pandemic to permanently impact the services or products they offer as well as their supply chains.
Keywords: digital economy; business review; digital technology; investment